2020
DOI: 10.2337/db19-1057
|View full text |Cite
|
Sign up to set email alerts
|

Maintaining Myocardial Glucose Utilization in Diabetic Cardiomyopathy Accelerates Mitochondrial Dysfunction

Abstract: Cardiac glucose uptake and oxidation are reduced in diabetes despite hyperglycemia. Mitochondrial dysfunction contributes to heart failure in diabetes. It is unclear whether these changes are adaptive or maladaptive. To directly evaluate the relationship between glucose delivery and mitochondrial dysfunction in diabetic cardiomyopathy, we generated transgenic mice with inducible cardiomyocyte-specific expression of the GLUT4. We examined mice rendered hyperglycemic following lowdose streptozotocin prior to inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
55
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(55 citation statements)
references
References 60 publications
0
55
0
Order By: Relevance
“…Other evidence supporting this hypothesis was achieved by Yan et al, using transgenic mice with cardiac-specific overexpression of GLUT1 [ 179 ]; the authors demonstrated how augmented rates of myocardial glucose uptake and oxidation can predispose the heart to impaired function. To further address the mechanism by which glucose might alter the cardiac function, Wende et al [ 180 ] investigated the consequences to restore glucose delivery in a context of short-term diabetes onset using transgenic mice with inducible cardiac-specific expression of GLUT4. This study showed that the increased myocardial glucose delivery associates with an accelerated mitochondrial dysfunction in diabetic cardiomyopathy, indicating how reducing the glucose uptake during uncontrolled hyperglycemic conditions could represent an important therapeutic intervention to limit glucotoxicity.…”
Section: Cardiometabolic Adaptations In Heart Failure and Chronic mentioning
confidence: 99%
See 1 more Smart Citation
“…Other evidence supporting this hypothesis was achieved by Yan et al, using transgenic mice with cardiac-specific overexpression of GLUT1 [ 179 ]; the authors demonstrated how augmented rates of myocardial glucose uptake and oxidation can predispose the heart to impaired function. To further address the mechanism by which glucose might alter the cardiac function, Wende et al [ 180 ] investigated the consequences to restore glucose delivery in a context of short-term diabetes onset using transgenic mice with inducible cardiac-specific expression of GLUT4. This study showed that the increased myocardial glucose delivery associates with an accelerated mitochondrial dysfunction in diabetic cardiomyopathy, indicating how reducing the glucose uptake during uncontrolled hyperglycemic conditions could represent an important therapeutic intervention to limit glucotoxicity.…”
Section: Cardiometabolic Adaptations In Heart Failure and Chronic mentioning
confidence: 99%
“…Starting from the assumption that under pathological conditions, the shift of the heart to a glucose metabolism is an adaptive/protective stratagem [ 199 ], the promotion of carbohydrate utilization may represent a useful therapeutic strategy. Nonetheless, as previously mentioned, the presence of uncontrolled hyperglycemia may worsen cardiac function by glucotoxicity in diabetic patients [ 180 ].…”
Section: Therapeutic Strategies In Cardiac Diseasesmentioning
confidence: 99%
“…Meantime, studies suggest that the recruitment of GLUT4 to the membrane is essential for the glucose uptake process (Thorens B et al, 2010). Decreased protein expression and translocation of GLUT4 to the cell surface in cardiomyocytes have been found in both types and diabetes mellitus (Essandoh K et al, 2020;Wende AR et al, 2020;Yuan Y et al, 2019). Additionally, research shows that AS160 knockdown was shown to result in a partial re-distribution of GLUT4 from intracellular compartments to the membrane, a concomitant increase in basal glucose uptake, and a 3-fold increase in basal GLUT4 exocytosis (Wende AR et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Decreased protein expression and translocation of GLUT4 to the cell surface in cardiomyocytes have been found in both types and diabetes mellitus (Essandoh K et al, 2020;Wende AR et al, 2020;Yuan Y et al, 2019). Additionally, research shows that AS160 knockdown was shown to result in a partial re-distribution of GLUT4 from intracellular compartments to the membrane, a concomitant increase in basal glucose uptake, and a 3-fold increase in basal GLUT4 exocytosis (Wende AR et al, 2020). Besides, a study indicates that PI3K/AKT pathway works as upstream signaling to stimulate the GLUT4 translocation to the cell surface in cardiomyocytes, thereby promoting glucose uptake (Yuan Y et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies used transgenic mice that rendered T1D-like streptozotocin (or control) and that inducibly overexpress the glucose transporter GLUT4 in cardiomyocytes. First, in the non-diabetic mice, increased uptake of glucose decreased mitochondrial ATP generation, and by echocardiography, the mice displayed evidence of diastolic dysfunction [ 60 ]. In animals with pre-established T1D, inducible expression of GLUT4 in cardiomyocytes drove mitochondrial oxidative dysfunction.…”
Section: Diabetes and Consequences For Mitochondrial Health — Pathways To Cardiovascular Diseasesmentioning
confidence: 99%